NEUROFEEDBACK INFLUENCE ON CEREBRUM BIOELECTRICAL ACTIVITY IN GYMNASTS-WOMEN - T. Yu. Strizhkova; L. P. Cherapkina; O. Yu. Strizhkova (Бюллетень сибирской медицины, 2013)
The analysis of electroencephalogram (EEG) of highly skilled gymnasts-women (main group – 49, control group – 39) showed the availability of cerebrum bioelectrical activity features of sportswomen connected with left hemisphere dominance, predominance of theta-rhythm power and lower reaction to eyes closing, also character of neurodynamic changes generated by neurofeedback course depended on ovarian-menstrual cycle phases.